Optimal Policies of Social Infrastructures Maintenance using Shock and Damage Model - Akihiro Yamane (International Journal of Mathematical, Engineering and Management Sciences, 2021)
Social infrastructures such as roads and bridges are indispensable for our lives. They have to be maintained continuously and such maintenance has become a big issue in Japan. Social infrastructures are maintained under strict restrictions such as decreasing in local finance revenue and scarcity of skilful engineers. Various kinds of factors such as inspection periods, maintenance costs, and degradation levels, are necessary to consider in establishing efficient maintenance plans of social infrastructures. Furthermore, the special circumstances of social infrastructures such as the delay of constructions which is caused by the scarcity of budget, must be discussed for the efficient maintenance plan. For such discussion, the stochastic cost model which contains preventive and corrective maintenances is useful. Although these models have been studied in mechanical and electronic systems, unique characteristics of social infrastructures such as their enormous scale and delays due to maintenance budget restrictions must be considered when such social infrastructure models are discussed. In this paper, we establish maintenance models of infrastructures which some of preventive maintenance must be prolonged. The expected maintenance cost rate is established using the cumulative damage model and optimal policies which minimizes them are considered. Three basic models and their extended models which consider natural disasters are discussed.